2015
DOI: 10.1017/s1355617715000922
|View full text |Cite
|
Sign up to set email alerts
|

Do Subjective Memory Complaints Lead or Follow Objective Cognitive Change? A Five-Year Population Study of Temporal Influence

Abstract: Objective The relationship between subjective memory complaints (SM) and objective memory (OM) performance in aging has been variably characterized in a substantial literature, to date. In particular, cross-sectional studies often observe weak or no associations. We investigated whether subjective memory complaints and objectively measured cognition influence each other over time, and if so, which is the stronger pathway of change – objective to subjective, or subjective to objective – or whether they are both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 84 publications
6
59
1
Order By: Relevance
“…The relationship between subjective cognitive complaints and objective performance is not clear and the inconsistency described in previous studies may be related to sample characteristics, but also the instruments used to measure both complaints and objective performance. Our results are consistent with other studies investigating homogeneous samples with high β-amyloid burden or APOE ε4 carriers6891011121314, where a positive association has been described. As recently claimed, the association between subjective and objective memory do exists but is nuanced6.…”
Section: Discussionsupporting
confidence: 93%
“…The relationship between subjective cognitive complaints and objective performance is not clear and the inconsistency described in previous studies may be related to sample characteristics, but also the instruments used to measure both complaints and objective performance. Our results are consistent with other studies investigating homogeneous samples with high β-amyloid burden or APOE ε4 carriers6891011121314, where a positive association has been described. As recently claimed, the association between subjective and objective memory do exists but is nuanced6.…”
Section: Discussionsupporting
confidence: 93%
“…The strength of these mutual relations between abilities are captured in the M matrix in the mutualism model and can be both unidirectionalas for example in investment theory where growth in crystallized intelligence is fueled by niet growth in, maar juist 'level' fluid intelligence Cattell (1971) -or bidirectional. These bidirectional facilitating relations have previously been observed between the development of cognitive strategies and short-term memory (Siegler and Alibali, 2005), vocabulary and reading ability (Quinn et al, 2015) and between subjective and objective memory in aging (Snitz et al, 2015). In mathematics, van der Ven et al (2012) found a positive interactions between changes in math skills and changes in working memory, suggesting mutual influences in their development.…”
Section: Two Different Theories Of Cognitive Developmentsupporting
confidence: 56%
“…While this is consistent with some studies (Cargin et al, 2008; Pearman et al, 2014), several studies, after controlling for depressive symptoms, found correlated longitudinal changes between self-SCC and OM. (Hulur et al, 2015; Parisi et al, 2011; Snitz et al, 2015; Zimprich & Kurtz, 2015). Methodological differences may partially account for some of this inconsistency in that our study included a brief total longitudinal time-frame (mean interval across 3 visits = 4 years), with a relatively healthy and younger cohort (Visit 1 mean = 58 years) that may be exhibiting stable performance on OM compared to older individuals.…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…Additional limitations include our separate linear mixed effects models approach, as several studies reporting covariation between SCC and OM used latent growth curve modeling (Hulur et al, 2015; Mascherek & Zimprich, 2011; Parisi et al, 2011; Snitz et al, 2015; Zimprich & Kurtz, 2015); which could be particularly useful as our sample ages and likelihood of variability in cognitive function increases. Also, the low test–retest reliability of the IQCODE is inconsistent with previous reliability measurements (Jorm & Jacomb, 1989; Jorm, Scott, Cullen, & MacKinnon, 1991; Jorm, 2004) and again may be partially due to the relatively healthy status and younger age of our sample.…”
Section: Limitations and Conclusionmentioning
confidence: 99%